2014
DOI: 10.1073/pnas.1400128111
|View full text |Cite
|
Sign up to set email alerts
|

YY1 is indispensable for Lgr5 + intestinal stem cell renewal

Abstract: The intestinal stem cell fuels the highest rate of tissue turnover in the body and has been implicated in intestinal disease and cancer; understanding the regulatory mechanisms controlling intestinal stem cell physiology is of great importance. Here, we provide evidence that the transcription factor YY1 is essential for intestinal stem cell renewal. We observe that YY1 loss skews normal homeostatic cell turnover, with an increase in proliferating crypt cells and a decrease in their differentiated villous proge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 63 publications
6
60
0
Order By: Relevance
“…Similarly, YY1 was shown to regulate adipocyte differentiation, in that overexpression of YY1 in 3T3-L1 cells decreased differentiation and YY1 knockdown increased differentiation (58). More global gene expression analyses in cells from mice that conditionally deleted YY1 specifically in muscle cells, or in intestinal epithelial stem cells, indicated that the major pathways down-regulated in both types of knockout mice were mitochondrial bioenergetics pathways (59,60). The intestinal epithelial stem cells also revealed up-regulation of cell cycle genes, and ChIP-seq in these cells showed enrichment for RNA processing and mitochondrial functions.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, YY1 was shown to regulate adipocyte differentiation, in that overexpression of YY1 in 3T3-L1 cells decreased differentiation and YY1 knockdown increased differentiation (58). More global gene expression analyses in cells from mice that conditionally deleted YY1 specifically in muscle cells, or in intestinal epithelial stem cells, indicated that the major pathways down-regulated in both types of knockout mice were mitochondrial bioenergetics pathways (59,60). The intestinal epithelial stem cells also revealed up-regulation of cell cycle genes, and ChIP-seq in these cells showed enrichment for RNA processing and mitochondrial functions.…”
Section: Discussionmentioning
confidence: 97%
“…YY1 ChIP-seq peaks were obtained from a previous study that identified YY1 binding sites in adult intestinal epithelium (GSM1295000) (Perekatt et al, 2014). Genes within 30 kb regions of YY1 binding sites were overlapped with genes downregulated in intestinal epithelium upon YY1 loss (log 2 FC<−0.27 and Benjamini-Hochberg adjusted P<0.05, Table S1).…”
Section: Informatics Analysismentioning
confidence: 99%
“…YY1 also regulates mitochondrial genes, as it has been implicated in the maintenance of mitochondrial structure and function as well as in regulating oxidative phosphorylation and other ATP-yielding processes (Blattler et al, 2012;Perekatt et al, 2014). The molecular pathway through which YY1 acts to regulate these functions is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…As additional evidence that mitochondrial functions are significant in adult stem cell biology, the YY1 transcription factor, a regulator of nuclear genes encoding mitochondrial proteins, is required for intestinal stem cell renewal [60]. Mitochondrial DNA (mtDNA) mutations typical of oxidative damage arise frequently in intestinal stem cells [61], also suggesting a role for ROS generated by mitochondrial oxidative phosphorylation.…”
Section: Adult Stem Cellsmentioning
confidence: 99%